PENGARUH KOMITE AUDIT DAN KUALITAS AUDIT EKSTERNAL TERHADAP TINDAKAN MANAJEMEN LABA - Fitria Kusumaningtyas Wijayanti; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2020)
This study aims to analyze the relationship between the audit committee and the interaction between the audit committee with the quality of the external audit on earnings management in manufacturing industry companies listed on Indonesia Stock Exchange in 2017 and 2018. The dependent variable used in this study is earnings management. The independent variable used is the expertise of the audit committee. Furthermore, the moderating variable in this study is the quality of the external audit which is proxied by the reputation of the auditor and auditor industry specialization. The control variables to maintain the relationship between the independent and dependent variables used are firm size and leverage.This study uses secondary data from annual reports and financial statements of manufacturing industry companies listed on the Indonesia Stock Exchange in 2017 and 2018. The sampling method used was purposive sampling. The sample in this study consists of 212 companies. Multiple linear regression analysis is the analysis used to test the hypothesis in this study.The test results in this study indicate that the audit committee has a negative effect on earnings management, the interaction between the audit committee and the auditor's reputation has no effect on earnings management and the interaction between the audit committee and the auditor industry specialization has a negative effect on earnings management.